TINGKAT KECEMASAN SISWA DALAM MENGHADAPI PEMBELAJARAN ONLINE DI KELAS XII SMA PURNA MANUNGGAL - Yoga Indrawan; Rosmawati Rosmawati; Khairiyah Khadijah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to find out the description of student anxiety level as well as analysis of aspects of apprehension, aspects of concern and aspects of fear in the face of online learning in class XII SMA PM. This type of research is descriptive-quantitative research, the research method used is survey research that basically focuses on one or more aspects of the research object. The instruments used in this study are questionnaires and researchers have conducted tests on the validity and reliability of SPSS version 22. Researchers collected data through online questionnaires using the Google form feature. The population in this study amounted to 68 students from class XII MIPA and XII IIS, sampling using cluster random sampling and obtained a sample of 33 students from class XII IIS. The results showed that the level of anxiety of students in PM SMA was in the category of severe and very severe anxiety. So it can be concluded that learning with the online method is still difficult to implement in SMA PM because it can cause student anxiety.Key Words: Survey, Anxiety, Online Learning.